(untitled) (European Journal of Education, 2020)
A major goal of schools is to provide students with knowledge and skills applicable (Csapó, 1998). However, teachers have to deal with the misconceptions of their students described as ideas based on experience leading to faulty understanding or naïve ideas (Martin et al., 2002). Schools are of primary importance in transmitting health-related knowledge, skills, attitudes and responsibilities, and health education provided by teachers is key in fighting against the health misconceptions students bring from their immediate environment and those transmitted by the Media. The aim of the present study was to pilot the research questionnaire designed to measure the health misconceptions of teacher trainees. The pilot sample contained 68 students. The research tool was an anonymous, self-administered questionnaire (Chronbach’s Alpha: 0.878) containing open-ended questions referring to the participants’ understanding of health, as well as multiple-choice questions on health misconceptions, together with background socio-demographic questions. From among the holistic dimensions of health (physical, mental, emotional, spiritual, societal, social) the physical dimension dominated the health concept of the respondents (95.2 percent). Looking at the sample mean, they correctly assessed that lifestyle (43 percent) plays the most important role in the development of their health. From among the 37 presented health statements, misconceptions could be detected in case of 23 statements (62 percent). The source of their existing misconceptions about health was the Media and family members. Our research intends to show which areas of health should be addressed more among future educators and thus indirectly among students, which misconceptions are worth clarifying at the outset.